Hubungan Pengetahuan dan Sikap dengan Perilaku Hygiene Penjamah Makanan pada Warung Makan - Alghifari, Razhiqa Syahru; Porusia, Mitoriana (Journal of Telenursing (JOTING), 2024)
This research aims to determine the relationship between knowledge and attitudes and the hygiene behavior of food handlers at food stalls. This research was located at a food stall in the Gonilan Village area, Kartasura District, Sukoharjo Regency. The method used is analytical observational and uses a cross-sectional design. The sampling technique used in this research was purposive sampling using the inclusion criteria of the respondent being a food handler, aged >18 years, and the inclusion criteria for a food stall being a fixed or permanent building located in the Gonilan area. This research used questionnaire instruments and observation sheets with a sample size of 106 food handler respondents from 40 food stalls in Gonilan Village. The results showed that (36.8%) the majority of food handler respondents were aged 26-35 years, (63.2%) the majority of food handler respondents were men, (78.3%) of food handler respondents had completed high school education. /Equivalent, and (50.9%) food handler respondents have worked for < 5 years. From the results of the univariate analysis, 55 (51.9%) food handler respondents tended to have good knowledge, 60 (56.6%) food handler respondents tended to have a positive attitude, and 55 (51.9%) food handler respondents had good behavior. The research conclusion shows that there is a relationship between knowledge (p-value 0.020) and attitude (p-value 0.013) with the hygiene behavior of food handlers at food stalls in the Gonilan Village area. There needs to be increased supervision and better guidance by food stall owners, health centers and related agencies. Keywords: Hygiene, Food Handlers, Knowledge, Behavior, Attitudes.